Self- and parent-reported depressive symptoms rated by the mood and feelings questionnaire. (October 2018) - Eg, Julie; Bilenberg, Niels; Costello, Elizabeth J.; Wesselhoeft, Rikke
Highlights: Girls report more depressive symptoms than boys. Parents report fewer depressive symptoms than the offspring itself. Depressive symptoms in children and adolescents do not increase with increasing age. Cognitive symptoms seem to be the best predictors of high depression scores. The risk of self-selection and non-response bias in voluntary participation is high. Abstract: The Mood and Feelings Questionnaire (MFQ) was developed to measure depressive symptoms in children and adolescents. It includes a self-report and a parent-report part. This study set out to test the psychometric properties of the MFQ in a Danish population of children and adolescents.The study included a population-based sample of n  = 992 individuals aged 9–17 years and n  = 703 parents from five schools. The internal consistencies of both MFQ versions were excellent with high alpha coefficients. With few exceptions, correlation between items and the total score was moderate to high. Vegetative symptoms were among the lowest correlating items while cognitive symptoms were among the highest. Girls reported more depressive symptoms than boys, and reports from offspring indicated more depressive symptoms than reports from parents. There was no difference in depressive symptoms by respondents aged 9 to 11 compared to respondents aged 12 to 17 in schools where all pupils participated. However, in schools where pupils participated by choice, an increase in depressive symptoms by age was found. This study suggests that MFQ is reliable for evaluating depressive symptoms in a population of children and adolescents. Furthermore, it is of clinical relevance that parents tend to underreport depressive symptoms of their offspring.